2004
DOI: 10.1093/hmg/ddh236
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic analysis of neurofilament light gene mutations linked to Charcot-Marie-Tooth disease in cell culture models

Abstract: Mutations in the neurofilament light (NFL) gene cause Charcot-Marie-Tooth (CMT) disease. There is a wide range of clinical presentations in CMT patients harboring NFL mutations, with patients classified as CMT2E or CMT1F. In this study, we analyzed the effects of five NFL mutations on the assembly and intracellular distribution of intermediate filaments (IFs), and compared the results with those obtained previously for other NFL mutations. Although all NFL mutants affected the formation of IF networks, our dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
63
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(71 citation statements)
references
References 48 publications
8
63
0
Order By: Relevance
“…The pathology overlaps with the previously described GAN, which is also classified as a neuronal CMT (72). A number of CMT-associated NEFL mutations have been tested for their ability to self assemble and coassemble with wild-type NFTPs (80). The results showed that all pathogenic mutations disrupted the assembly and transport of neuronal IFs.…”
Section: Neuronal If Inclusion Disease a Recently Described Disease mentioning
confidence: 58%
“…The pathology overlaps with the previously described GAN, which is also classified as a neuronal CMT (72). A number of CMT-associated NEFL mutations have been tested for their ability to self assemble and coassemble with wild-type NFTPs (80). The results showed that all pathogenic mutations disrupted the assembly and transport of neuronal IFs.…”
Section: Neuronal If Inclusion Disease a Recently Described Disease mentioning
confidence: 58%
“…5,6 The mutation carried by our patients that leads to a substitution of glutamic acid to lysine at position 396 (Glu396Lys) occurs in a highly conserved motive at the end of the rod domain, and several families with the same mutation as well as a transgenic mouse model have been reported in literature. [5][6][7]18,19 The axons of the mutant mouse had fewer NFs than those of the wild-type, and accordingly, sural nerve biopsies from patients have shown the presence of axons either devoid of or with a variable density of NFs. Our results from both immunohistochemistry and WB analysis are in keeping with these data, demonstrating reduced levels of NFs in cutaneous nerve fibers.…”
Section: 12mentioning
confidence: 96%
“…4 NEFL mutations are distributed throughout the 3 functional domains of the NF-L (head, rod, and tail) and different mutations have been shown to lead to distinct pathologic effect. 5,6 Previous studies in a transgenic mouse model carrying a Glu396Lys have demonstrated accumulation of NFs in the neuronal cell body, with decreased NFs in axons. 6 Sural nerve biopsies from patients with the Glu396Lys have shown the presence of axons with a variable density of NFs.…”
mentioning
confidence: 99%
“…Charcot-Marie-Tooth disease (CMT) is the most common inherited peripheral neuropathy affecting motor and sensory nerves of the peripheral nervous system (29). In CMT, disruption of assembly and aggregation of NF-L occur from mutations of NF-L (30,31). Recently, it was reported that CMT mutations of NF-L and small heat-shock protein B1 have similar disruptive effects on the NF network, leading to aggregation of NF-L protein with progressive degeneration and loss of viability of motor neurons (32).…”
Section: Resultsmentioning
confidence: 99%